Conventional Dendritic Cells and Slan+ Monocytes During HIV-2 Infection - Iannetta, Marco; Isnard, Stéphane; Manuzak, Jennifer; Guillerme, Jean-Baptiste; Notin, Mathilde; Bailly, Karine; Andrieu, Muriel; Amraoui, Sonia; Vimeux, Lene; Figueiredo, Suzanne; Charmeteau-de Muylder, Bénédicte; Vaton, Laura; et al. (Frontiers in Immunology, 2020)
HIV-2 infection is characterized by low viremia and slow disease progression as compared to HIV-1 infection. Circulating CD14++CD16+ monocytes were found to accumulate and CD11c+ conventional dendritic cells (cDC) to be depleted in a Portuguese cohort of people living with HIV-2 (PLWHIV-2), compared to blood bank healthy donors (HD). We studied more precisely classical monocytes; CD16+ inflammatory (intermediate, non-classical and slan+ monocytes, known to accumulate during viremic HIV-1 infection); cDC1, important for cross-presentation, and cDC2, both depleted during HIV-1 infection. We analysed by flow cytometry these PBMC subsets from Paris area residents: 29 asymptomatic, untreated PLWHIV-2 from the IMMUNOVIR-2 study, part of the ANRS-CO5 HIV-2 cohort: 19 long-term non-progressors (LTNP; infection ≥8 years, undetectable viral load, stable CD4 counts≥500/µL; 17 of West-African origin -WA), and 10 non-LTNP (P; progressive infection; 9 WA); and 30 age-and sex-matched controls: 16 blood bank HD with unknown geographical origin, and 10 HD of WA origin (GeoHD). We measured plasma bacterial translocation markers by ELISA. Non-classical monocyte counts were higher in GeoHD than in HD (54 vs 32 cells/µL, p=0.0002). Slan+ monocyte counts were twice as high in GeoHD than in HD (WA: 28 vs 13 cells/µL, p=0.0002). Thus cell counts were compared only between participants of WA origin. They were similar in LTNP, P and GeoHD, indicating a population- rather than HIV-2-related difference. cDC counts did not show major differences between the groups. Interestingly, inflammatory monocyte counts correlated with plasma sCD14 and LBP only in PLWHIV-2, especially LTNP, and not in GeoHD. In conclusion, in LTNP PLWHIV-2, inflammatory monocyte counts correlated with LBP or sCD14 plasma levels, indicating a potential innate immune response to subclinical bacterial translocation. As GeoHD had higher inflammatory monocyte counts than HD, our data also show that specific controls are important to refine innate immunity studies.